2010
DOI: 10.1371/journal.pone.0012112
|View full text |Cite|
|
Sign up to set email alerts
|

Rad21-Cohesin Haploinsufficiency Impedes DNA Repair and Enhances Gastrointestinal Radiosensitivity in Mice

Abstract: Approximately half of cancer-affected patients receive radiotherapy (RT). The doses delivered have been determined upon empirical experience based upon average radiation responses. Ideally higher curative radiation doses might be employed in patients with genuinely normal radiation responses and importantly radiation hypersensitive patients would be spared the consequences of excessive tissue damage if they were indentified before treatment. Rad21 is an integral subunit of the cohesin complex, which regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 52 publications
6
77
0
2
Order By: Relevance
“…41 Furthermore, it also directly regulates transcription of genes implicated in pluripotency, cell proliferation, and differentiation, 37 and monoallelic loss of RAD21 has been associated with impaired bone marrow stem cell clonogenic regeneration, while homozygous deletion results in early embryonic death. 42 In addition, in siRNA-based screens, RAD21 was recently also identified as a functional epigenetic silencing factor along with other genes like DNMT3A, and TRIM24, both of which are also mutated in AML. 43 The chromosomal coordinates refer to the human reference genome hg19 (GRCh37).…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, it also directly regulates transcription of genes implicated in pluripotency, cell proliferation, and differentiation, 37 and monoallelic loss of RAD21 has been associated with impaired bone marrow stem cell clonogenic regeneration, while homozygous deletion results in early embryonic death. 42 In addition, in siRNA-based screens, RAD21 was recently also identified as a functional epigenetic silencing factor along with other genes like DNMT3A, and TRIM24, both of which are also mutated in AML. 43 The chromosomal coordinates refer to the human reference genome hg19 (GRCh37).…”
Section: Discussionmentioning
confidence: 99%
“…The examined markers correlated with each other, partially unraveling the network of genes involved in endometrial tumorigenesis. Findings of previous studies have suggested that the decreased expression of cohesins results in an inappropriate increase in homologous recombination which may drive tumorigenesis through the promotion of genomic instability, such as loss of heterozygosity (15,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of cohesin expression and cohesin-regulated genes is common in numerous types of human cancer (8)(9)(10)(11)(12)(13), including endometrial cancer (14). Furthermore, cohesin-defective cells have been discovered to be sensitive to ionizing radiation and DNA-damaging drugs (8,15).…”
Section: Introductionmentioning
confidence: 99%
“…To date, both in vitro and in vivo data demonstrate that RAD21 expression influences cellular sensitivity to DNA-damaging agents such as those used in chemotherapy or chemoradiotherapy (Atienza et al, 2005;Bauerschmidt et al, 2010;Xu et al, 2010;Xu et al, 2011a, b). An increased susceptibility of cancer cell lines to conventional chemotherapeutics was demonstrated following knockdown of RAD21 or other cohesin gene (Atienza et al, 2005;Xu et al, 2011b;Supernat et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…During the G1 phases of the cell cycle, the cohesin complex is thought to form a ring and entrap DNA helices and, with the aid of several accessory and regulatory proteins, facilitates binding of newly formed sister chromosomes and appropriate chromosome segregation during anaphase (Haering et al, 2008). The cohesin complex is also implicated in several other important processes including homologous recombinational repair or DNA damage (Birkenbihl and Subramani, 1992;Nasmyth et al, 2001;Sonoda et al, 2001;Watrin and Peters, 2006), in particular double-stranded breaks (Birkenbihl and Subramani, 1992;Bauerschmidt et al, 2010;Xu et al, 2010), cell cycle checkpoint control (Watrin and Peters, 2009), chromatin remodelling (Hakimi et al, 2002), gene regulation (Supernat et al, 2012) and prevention of read-through transcription. Presence of this versatile complex in subcellular locations outside the nucleus and within extracellular matrix has also been observed; however, the exact purpose of cohesin in these instances is unknown.…”
mentioning
confidence: 99%